(untitled) (Journal of Philosophy Culture and Political Science, 2019)
Khodzha Akhmet Yasaui is a founder of Turkish branch of Sufi zm, thinker, poet. Only the date of death is known - 1166. His work «Divan and khikmet» has preserved to present days («Book of wisdom» - often briefl y used under the name of «Khikmets»). Akhmet’s father Ibragim was the known as sheik in Sayram. Personal formation of Akhmet is related to the city Yasy (one of the former names Turkistan from VI to XV sentures.), later he was sent to Bukhara, where passed apprenticeship at Khamadani. Purchasing dignity of connoisseur of Sufi zm, Yasaui came back in Yasy and continued tradition, stemmed from Arystanbab. He conducted the last years of his life in a cave (now it is found and restored). Built in honour of Akhmet Yasaui with oreder and plans of Timur the mausoleum (khanakis a masterpiece of medieval architecture of Kazakhstan. Akhmet Yassaui occupies the special place in development of Sufi idea of sense of life. Akhmet Yassaui asserted that God is present everywhere and in everything. In opinion of A.Yassaui, every person has the ability to perfection. For achievement of veritable sense of destiny a man has freedom, granted by God with a certain goal. Keywords: God, world, religions, ideology, mind, nomanilasim, conscious.